Control and quality assessment of medical services in requirements of all-union state standard ISO 9001:2009 - Хімічева, Ганна Іванівна; Пономаренко, Наталія Анатоліївна (Eastern-European Journal of Enterprise Technologies, 2010)
The article analyzes the current state of the quality of medical services in Ukraine and abroad and shows that in Germany and Switzerland adopted ISO 9001 as national. The technique for monitoring and assessing the quality of medical services in medical institutions.